The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/pat.2068
|View full text |Cite
|
Sign up to set email alerts
|

Electrokinetic and electrorheological properties of poly(vinyl chloride)/polyindole conducting composites

Abstract: In this study, poly(vinyl chloride) (PVC), polyindole (PIN), and PVC/PIN conducting composites having five different compositions were used. Particle sizes, densities, dielectric constants, and sedimentation ratios of the materials were determined. The zeta‐potentials of the samples were measured in aqueous and nonaqueous (silicone oil [SO]) media. The dispersions prepared in SO were subjected to external electric field strength, and their electrorheological properties were investigated. Then the effects of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…This structural arrangement makes PIn and its derivatives of great interest in various applications . Methods for the synthesis of PIn include electrochemical, chemical oxidative, interfacial, and emulsion polymerization . However, few studies have examined the electrorheological measurements of polyindole.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This structural arrangement makes PIn and its derivatives of great interest in various applications . Methods for the synthesis of PIn include electrochemical, chemical oxidative, interfacial, and emulsion polymerization . However, few studies have examined the electrorheological measurements of polyindole.…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have examined the electrorheological measurements of polyindole. Unal et al . have investigated the electrorheological and viscoelastic properties of PIn and its composites.…”
Section: Introductionmentioning
confidence: 99%
“…With this specific aim lot of researchers have made their contribution to the felid such as Sari et al reported synthesis, characterization, ER and creep-recovery properties of polyindole/polyethylene composites [10]. Koyuncu et al investigated the possibility of synthesizing a colloidally steady poly(vinyl chloride)/polyindole ER active composite system [11]. Tayalan et al prepared the conducting poly(vinyl chloride)/polyindole composites and freestanding films via chemical polymerization [12].…”
Section: Introductionmentioning
confidence: 98%
“…Motivated by the concerned intriguing physics as well as a possible plethora of applications, some electrokinetic properties of ERFs in the presence of surfactants have recently been discussed in the literature [57][58][59][60]. However, the problem of electro-osmosis of an ER fluid remains unaddressed.…”
Section: Introductionmentioning
confidence: 99%